Porous aligned ZnSr-doped β-TCP/silk fibroin scaffolds using ice-templating method for bone tissue engineering applications - Bicho, D. (2021)
The bone is a complex and dynamic structure subjected to constant stress and remodeling. Due to the worldwide incidence of bone disorders, engineered bone tissues have emerged as solution for bone grafting, which require sophisticated scaffolding architectures while keeping high mechanical performance. However, the conjugation of bone-like scaffold architecture with efficient mechanical properties is still a critical challenge for biomedical applications. In this sense, the present study is focused on the development of silk fibroin (SF) scaffolds crosslinked with horseradish peroxidase and mixed with zinc (Zn) and strontium (Sr)-doped β-tricalcium phosphate (ZnSr.TCP) to mimic bone structures. The ZnSr.TCP-SF hydrogels were tuned in programmable ice-templating parameters, and further freeze-dried, to obtain 3D scaffolds with controlled pore orientation. The results showed interconnected channels in the ZnSr.TCP-SF scaffolds that mimic the porous network of the native subchondral bone. The architecture of the scaffolds was characterized by microCT and showing tunable pore size according to freezing temperatures (-196 ºC: ~80.2 ± 20.5 µm; -80 ºC: ~73.1 ± 20.5 µm; -20 ºC: ~104.7 ± 33.7 µm). The swelling ratio, weight loss, and rheological properties were also assessed, revealing that the scaffolds were able to keep their integrity and morphology after aqueous immersion. Thus, the ZnSr.TCP-SF scaffolds made of aligned porous structure were developed as affordable candidates for future applications in clinical osteoregeneration and in vitro bone tissue modelling.